Leveraging learning experiences to promote student engagement in a business ethics class - Dickie, Carolyn; Pick, David; Issa, Theodora (University of Salford, 2011)
The number of students choosing to undertake business education has expanded dramatically over the past two decades concomitantly with exponential growth in business courses offered. However, the focus tends to be on the ‘business of business’ while the ethical, moral and social responsibility of business practice is neglected. This study evaluates students’ responses to a new approach to teaching business ethics to an undergraduate cohort; a new,creative teaching model emphasizing a unique learning experience designed to encourage students to experience critical thinking, to analyse and synthesise ethical situations and reflect upon their learning experience. The model, with the acronym S.T.A.R - See, Talk, Act and Review - was introduced. Students were provided with conceptual tools and techniques to examine, act and reflect on ethical issues. Using a mixed methods approach, students’ responses to the course were collected and their views of the new approach examined. Results suggest that, as well as a discernible shift in their view of the place of ethics in business, students have been far more engaged in the course and developing their learning experience.